2020
DOI: 10.1016/j.eap.2020.09.003
|View full text |Cite
|
Sign up to set email alerts
|

Does ICT maturity catalyse economic development? Evidence from a panel data estimation approach in OECD countries

Abstract: To date, definitions of information and communication technology (ICT) development used in quantitative studies on the relationship between economic development and ICT are incomplete and often based on single indicators. Thus, this study investigates the link between ICT maturity and economic development in the Organisation of Economic Cooperation and Development (OECD) countries. A novel composite index of ICT maturity that includes previously neglected dimensions of ICT maturity, such as affordability and q… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
17
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 24 publications
(17 citation statements)
references
References 70 publications
0
17
0
Order By: Relevance
“…The development of human capital, accompanied by the accumulation of knowledge and R&D, are important factors explaining technological innovation in G7 countries ( Wang et al, 2020 ). Research findings suggest that ICT maturity is associated with a 1–3.8% increase in economic development in OECD countries ( Ali et al, 2020 ). Similar empirical results were obtained studying the endogenous relationships between R&D, ICT infrastructure development and long-term economic growth in OECD countries during 1961–2018 ( Nair et al, 2020 ).…”
Section: Literature Reviewmentioning
confidence: 99%
See 1 more Smart Citation
“…The development of human capital, accompanied by the accumulation of knowledge and R&D, are important factors explaining technological innovation in G7 countries ( Wang et al, 2020 ). Research findings suggest that ICT maturity is associated with a 1–3.8% increase in economic development in OECD countries ( Ali et al, 2020 ). Similar empirical results were obtained studying the endogenous relationships between R&D, ICT infrastructure development and long-term economic growth in OECD countries during 1961–2018 ( Nair et al, 2020 ).…”
Section: Literature Reviewmentioning
confidence: 99%
“…In light of the evaluation of ICT use as an indicator of the digital divide and its relationship to digital development across countries, only a limited number of studies use a multi-level indicator approach ( Appiah-Otoo and Song, 2021 , Xu and Reed, 2021 , Habibi and Zabardast, 2020 , Ali et al, 2020 ). However, the use of the indicators on macro, business, infrastructural and individual levels, which are mentioned above, reflects the digital development of the country and digital inequality in Internet use in terms of its frequency, activity, use in the cloud more informatively.…”
Section: Literature Reviewmentioning
confidence: 99%
“…Grounded on prior studies, we assert that ICT maturity may catalyze economic growth, social cohesion, and environmental sustainability. 24 - 26 ICTs enable firms to be more productive at the fundamental level and improve the level of healthcare delivery. 27 Similarly, financial development may reduce pollutant emissions, 28 increase consumption of renewable energy, 29 and trade openness.…”
Section: Introductionmentioning
confidence: 99%
“…Many empirical studies have confirmed that information and communication technology (ICT) can promote the economic development of a nation, especially when a pandemic such as the Coronavirus Disease-2019 (COVID-19) is sweeping the world [1] , [2] . Both developing and developed countries have invested in ICT to resist the negative economic impact of the current COVID-19 pandemic [3] , such as the “working from home” model via ICT equipment [4] , [5] .…”
Section: Introductionmentioning
confidence: 99%